Celebrity gods: new religions, media, and authority in occupied Japan - Dorman, Benjamin (Nanzan library of Asian religion and culture, 2012)
Renmonkyō and the Meiji press -- Deguchi Onisaburō as a prewar model -- The birth of two celebrity gods -- Before Jikōson -- Building a "kingdom of god" -- Bureaucracy, religion, and the press under occupation -- Jikōson and Jiu -- Kitamura Sayo -- New religions and critics in the immediate postwar press